PENYULUHAN TENTANG MEWUJUDKAN KEMANDIRIAN DENGAN PENDIDIKAN BERASRAMA DI MA’HAD AL-ZAYTUN - Abdur Rahim; Nur Sabrina Fathimah; Alisatus Sina Asshobri; Naufal Ibnu Tsalis; Vania Indah Sabillah; Laili Nur Istiqomah; Muhammad Baldan Al-Kautsar; Luthfia Al Kanza (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Boarding education has an important role in shaping individual character, independence, and competence. This research examines counseling efforts to realize self-sufficiency through boarding education at Ma'had Al-Zaytun. Counseling was carried out in five different hostels, namely Al-Fajr, Al-Nur, Al-Madani, Al-Musthofa, and Friendship. Each dormitory has different goals and targets in order to increase students' self-awareness, responsibility and independence. This counseling about realizing independence through boarding school education at Ma'had Al-Zaytun aims to provide students with an understanding of the importance of independence in boarding school life. The implementation method is by providing counseling, followed by questions and answers to explore the students' understanding, apart from that, pre-tests and post-tests are also given to determine the students' level of understanding of the counseling material. The material provided in this counseling is adjusted to the age and needs of the students in each dormitory. The results of this counseling show an increase in understanding and application of the values ​​of independence in boarding life